Risk, intoxication and death: contemporary media framing of drug-related deaths - MacGregor, Susanne (Routledge handbook of intoxicants and intoxication, 2023)
The chapter considers changes in how the issue of death from drug intoxication has been viewed in recent years. As numbers of drug overdose deaths increased in several countries, a range of actors became involved in drawing attention to the issue, and the framing of the problem altered, along with associated proposed solutions. The media’s role in this shift of perceptions was significant, showing that the media occupy a space where contested views play out and which may come to influence state policies. The chapter locates contemporary framings within dominant competing policy paradigms (abstinence/prohibition versus regulation/harm reduction). Drug overdose deaths have been identified as a key ‘indicator’ and used to signify policy failure. Arguments tended to focus on the toxicity of substances, as well as the contribution of stigma, social marginalisation and isolation. Less attention has been paid to longer-term social determinants, although the concept of ‘deaths of despair’ has gained traction. Shifts in framing have led to some acceptance of the harm reduction approach but this remains a limited understanding, restricted to single interventions such as Safe Injecting Facilities or use of naloxone.